Between the sky and the sea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The economies of ACP island States, just as all other ACP States, depend largely on trading agreements with Europe and other Northern countries. Their economic vulnerability is compounded by their isolation, minuscule areas of available land,...